Majlis Apresiasi & Kecemerlangan Akademik sesi Oktober 2022 - Februari 2023 - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2023)
On 4th March 2023, AAGBS organised an event, “Majlis Apresiasi & Kecemerlangan Akademik” at Hotel Mardhiyyah, Shah Alam. The event was attended by Prof Datin Dr Suzana Sulaiman (TNC Academic & Internationalization), Dato’ Sri Dr Irmohizam Ibrahim (AAGBS Brand Ambassador), Prof Dr Syed Jamal Abdul Nasir Syed Mohamad (Dean of AAGBS), staff and students of AAGBS. The event was held to appreciate the students’ academic success and involvement in ASAS as well as student mobility programs. The dress code for the hi-tea was “Traditional Malay”. The guests looked resplendent in their best traditional Malay attire. AAGBS thanks all who came to the event and made it successful.